Pain and the rate of dentinal fluid flow produced by hydrostatic pressure stimulation of exposed dentine in man - Panta Charoenlarp (2018)
Objective: To determine the relationship between pain intensity and the rate of fluid flow through dentine in human subjects. Design: The experiments were carried out on 16 premolars in 13 human subjects (aged 15-25 years). Dentine was exposed at the tip of the buccal cusp, etched with acid and covered with saline. A series of 5 s hydrostatic pressure stimuli between 400 mmHg above and 400 mmHg below atmospheric were applied to the dentine, in steps of 50 mmHg. The subject indicated the intensity of any pain produced on a visual analogue scale (VAS). The fluid flow through dentine during application of the same stimuli was measured in vitro within 3 h after tooth extraction. Results: The median pain threshold with negative (subatmospheric) stimuli was -125 mmHg and, with positive pressure stimuli, 200 mmHg, which corresponded to dentinal fluid flow rates of 3.29 nL/(s mm2) exposed dentine and 5.75 nL/(s mm2), respectively. Both the median pressure and the mean rate of flow at threshold with negative pressures were significantly lower than with positive pressures. The curves relating VAS score to stimulus intensity were similar with both negative and positive pressures. Conclusion: The sensory transduction mechanism for pain in human teeth is more sensitive to outward than inward flow through dentinal tubules. The difference in sensitivity was however much less than that of the hydrodynamic receptors in the cat, which respond very much more strongly to negative than positive pressure stimuli. © 2006 Elsevier Ltd. All rights reserved.